Teacher training: art as an intercessor in the experimentation of other ways of thinking - Crizel, Ana Paula; Rodrigues, Aline; Munhoz, Angélica Vier (Revista Eletrônica de Educação, 2016)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--> DOI: http://dx.doi.org/10.14244/198271991570 <!--[if gte mso 9]> <![endif]--> This text reports the experience of teacher training in higher education conducted by the Graduate Program in Teaching of the Department of Pedagogy at Univates, Brazil, along the first semester of 2014. The authors consider art as an important intercessor to think about curriculum and discourses in education and teaching. The art that has been blended with the contents studied in disciplines such as Curriculum Studies and Differences and Multiplicities is the art experienced by Nietzsche, art that is immanent to life and committed neither to beauty nor to ugliness, neither to methods nor to techniques. An art that favors sensitive encounters and potentializes life. In the first section, we present the focus of this paper, i.e., two trainings that have Pedagogy as a course, and art as an intercessor. The understanding of art by authors from the field of Philosophy of Difference is developed in the second section. The third section of this paper is divided into two parts, and presents experimentations performed in each one of the curriculum trainings. <span style="font-size: 11.0pt; line-height: 115%; font-family: ";Calibri";,";sans-serif";; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ";Times New Roman";; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Keywords<span style="font-size: 11.0pt; line-height: 115%; font-family: ";Calibri";,";sans-serif";; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ";Times New Roman";; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">: Art, Pedagogy, Teaching, Movement.<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Resumo Este texto relata a experiência do estágio de docência no Ensino Superior do Mestrado em Ensino do Centro Universitário UNIVATES, Brasil, que ocorreu no primeiro semestre de 2014 no curso de Pedagogia da instituição. As autoras aproximam-se da arte como importante intercessora, provocando movimentos para pensar o currículo e os discursos em educação e ensino. A arte que se misturou aos conteúdos de estudo das disciplinas Estudos do Currículo e Diferenças e Multiplicidades é aquela vivida por Nietzsche, uma arte imanente à vida, que não possui compromissos com o belo e o feio, com métodos e técnicas; uma arte que promove encontros sensíveis e potencializa a vida. Na primeira seção, apresenta-se a matéria que movimenta este artigo: dois estágios que possuem em comum um curso – o de Pedagogia – e um intercessor – a arte. A compreensão de arte operada pelos autores que percorrem o território da Filosofia da Diferença é desenvolvida na segunda seção. O terceiro momento deste artigo divide-se em duas partes, pois apresenta as experimentações desenvolvidas em cada um dos estágios curriculares. Palavras-chave: Arte, Pedagogia, Ensino, Movimento.<!--[if gte mso 9]> <w:LsdException Locked="false" Priority="19" SemiHidden="false" UnhideWhenUsed="false" QFormat="true" Nam